NARRATIVAS DE PRÁTICAS EM EDUCAÇÃO E TECNOLOGIA: A TRAJETÓRIA DO PROFESSOR DIGITAL - GALASSE, BRUNO TONHETTI (2016)
The purpose of this study is to report outstanding practices of basic education teachers who use Digital Information and Communication Technologies (TDIC) in school to foster new possibilities of knowledge construction in the didactic-pedagogical relationship with students: Kenski (1998), Livingstone 2011/2012), Prensky (2001). From those stories, it verifies how the TDICs contribute to a learning process that promotes critical and scientific reflections, based on the empowerment of the students (FREIRE, P., 2006) in their relationship with knowledge. The research subjects are teachers of the basic education from some public and private schools. For the teachers selection, it was identified those who have used technology in different contexts and approaches, not being the aim of this research the use of technology as a purpose itself, but its application as a support or tool for the development of students' learning in School. Through the (auto)biographical narrative research and the hermeneutic phenomenological approach brought by (FREIRE, 2012),it was possible to identify, from the stories of six teachers, to what extent the use of technology in classroom contributes and promotes a greater involvement and empowerment of the students, as well as how these teachers had contact with technology so it could be incorporated and seen as a possibility of developing their teaching work with the students